2015
DOI: 10.3399/bjgp15x683941
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ online access to their electronic health records and linked online services: a systematic review in primary care

Abstract: BackgroundOnline access to medical records by patients can potentially enhance provision of patient-centred care and improve satisfaction. However, online access and services may also prove to be an additional burden for the healthcare provider. AimTo assess the impact of providing patients with access to their general practice electronic health records (EHR) and other EHR-linked online services on the provision, quality, and safety of health care. Design and settingA systematic review was conducted that focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
196
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(203 citation statements)
references
References 43 publications
7
196
0
Order By: Relevance
“…From April 2015, patients have been able to access their primary care summary information online (8,9). Benefits to patients has been reported including increased control over their own health, greater understanding and improved adherence to both care plans and medications (9)(10)(11).…”
Section: Patient Access In Primary Carementioning
confidence: 99%
See 1 more Smart Citation
“…From April 2015, patients have been able to access their primary care summary information online (8,9). Benefits to patients has been reported including increased control over their own health, greater understanding and improved adherence to both care plans and medications (9)(10)(11).…”
Section: Patient Access In Primary Carementioning
confidence: 99%
“…In contrast access to health information can cause anxiety over security and privacy and can make patients feel less optimistic (10). Additional potential benefits include improved patient and MDT relationships, more empowered and satisfied patients, time saving, transparency, shared decisions, positive behavioural change and opportunities for education (9,10,(12)(13)(14). In some studies, online access has results in increase workload and usage of clinical services (9,15,16).…”
Section: Patient Access In Primary Carementioning
confidence: 99%
“…2 A recent systematic review found that patients reported benefits of online access in terms of experience, satisfaction, and feeling able to take control of their own health care, with possible advantages to patient safety when patients have online access to medication lists. 4,5 However, the same review concluded that we do not know whether online access translates into better health or health care for patients or whether it improves service efficiency. 4,5 poTenTiAL hArmS To recogniSe, diScuSS, And SAFeguArd AgAinST Like any policy, there is also potential for unintended harm and this is our focus here, particularly those harms related to privacy and confidentiality.…”
mentioning
confidence: 99%
“…4,5 However, the same review concluded that we do not know whether online access translates into better health or health care for patients or whether it improves service efficiency. 4,5 poTenTiAL hArmS To recogniSe, diScuSS, And SAFeguArd AgAinST Like any policy, there is also potential for unintended harm and this is our focus here, particularly those harms related to privacy and confidentiality. There has been no study on this topic as yet.…”
mentioning
confidence: 99%
See 1 more Smart Citation